2017
DOI: 10.1155/2017/3906306
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Its Determinants in Adults: A Sample from Community-Based Settings in the United Arab Emirates

Abstract: Background. Vitamin D deficiency (VDD) is a public health concern in adults worldwide. This study aims to explore the extent of VDD and its associated factors among adults in the United Arab Emirates (UAE). Subjects and Methods. Quantitative, cross-sectional research was used to assess VDD and its associated factors in 216 adults recruited from randomly selected community-based healthcare settings over a six-month period. Recent values of vitamin D and glycated hemoglobin (HbA1c) were abstracted from medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
3
25
3
1
Order By: Relevance
“…A random population study conducted in the individuals aged 35-65 years showed that there was no correlation between vitamin D levels and age (Rudnicki, Thode, Jorgensen, Heitmann, & Sorensen, 1993). Interestingly, we found that female individuals seemed to have lower serum levels of vitamin D in our studies, while some studies showed that there was no significant correlation between sex and vitamin D deficiency (Bani-issa et al, 2017). Most of these studies were carried on Western country in which taking part in outdoor exercise is encouraged.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A random population study conducted in the individuals aged 35-65 years showed that there was no correlation between vitamin D levels and age (Rudnicki, Thode, Jorgensen, Heitmann, & Sorensen, 1993). Interestingly, we found that female individuals seemed to have lower serum levels of vitamin D in our studies, while some studies showed that there was no significant correlation between sex and vitamin D deficiency (Bani-issa et al, 2017). Most of these studies were carried on Western country in which taking part in outdoor exercise is encouraged.…”
Section: Discussioncontrasting
confidence: 59%
“…No significant correlation between vitamin D levels and age was found, which is not consistent with some previous studies (Serdar et al., ). The previous studies insisted on that the serum levels of vitamin D were decreasing with the growth of age (Bani‐issa, Eldeirawi, Harfil, & Fakhry, ). Serum levels of vitamin D were tested in different age groups including the young and old population among these studies, while the subjects of our study were aged.…”
Section: Discussionmentioning
confidence: 99%
“…In the Emirates, Bani-Issa and colleagues performed a quantitative cross-sectional study in 2017 to assess vitamin D deficiency and the factors associated with this condition. The authors have concluded that the less-educated, employed Emirati participants had a significantly higher percentage of vitamin D deficiency than the higher-educated participants (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the Middle East and North Africa (MENA), especially the Kingdom of Saudi Arabia (KSA), high prevalence of vitamin D deficiency has been reported despite the abundance of sunshine (12,13). In 2015, a cross-sectional national multistage surveyreported that the prevalence of vitamin D deficiency was 40.6% in male Saudis and 62.65% in female Saudis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being located in high UV index area with sunny climate throughout the year, vitamin D insufficiency is known to be endemic in Gulf Region [20,21]. In studies done in Kuwait, Saudi Arabia and UAE the prevalence of hypovitaminosis D among adult population was reported to be 82.9% and 83.6% and 74%, respectively [22][23][24].…”
Section: Introductionmentioning
confidence: 99%